Effects of Sublingual Colostrum Application on Oral and Intestinal Flora of Extremely Low Birth Weight Infants - Wang, Hua; Li, Qiu-Fang; Xu, Xin-Fen; Hu, Xiao-Li (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: The aim of this study is to analyze the effects of colostrum application on the establishment of normal flora in the intestinal tracts and oral cavities of extremely low birth weight infants (ELBWI). Methods: A prospective cohort study design was adopted following the STROBE guidelines (Supplementary File 1). Colostrum was administered immediately after obtaining maternal breast milk using a special sterile cotton swab. There were no specific treatments for infants who did not receive colostrum. This experiment was completed on day 5 post-birth and the patients were divided into the colostrum and control groups, corresponding to whether or not colostrum was administered. Throat swabs and stool samples were collected on days 1 and 5 post-birth. Results: Using the conventional bacteria cultivation technique, the detection rate of bacteria in 98 cases of meconium at birth was 15.31%. On day 5, the detection rates of Staphylococcus in the colostrum and control groups were 36.54% and 34.78%, with no significant difference between them (P = 0.856), and that of Enterococcus was 26.92% and 13.04%, respectively, with no statistically significant difference (P = 0.089). Likewise, at birth, the detection rate of bacteria in 98 cases of throat swabs was 27.55%. On day 5, the detection rate of Streptococcus in the colostrum and control groups was 78.85% and 50.00%, respectively, recording a statistically significant difference this time (P = 0.003). Conclusion: Colostrum application had limited effects on intestinal flora colonization but contributes to physiological oral flora colonization.
Keywords: Bacteria culture